Using office referrals to examine discipline patterns: positive behavior support in a high school - Wiley, Cynthia Loe, author; Cooner, Donna, advisor; Carlson, Laurie, advisor (Colorado State University. Libraries, 2008)
The utility of systemic positive disciplinary frameworks such as school-wide positive behavior support (SWPBS) in high schools has not been determined. Most research to date has focused on elementary and middle schools that have instituted positive school-wide disciplinary frameworks with varying degrees of success. Similar research is necessary to determine if this type of disciplinary framework can be efficaciously applied at the high school level. The purpose of this three-year study was to describe discipline patterns in a comprehensive public high school pre- and post-implementation of a school-wide positive behavior support (SWPBS) system. Participants in the study were students from grades nine through twelve. The mean annual population of the school was 1,187. The research objective was to utilize longitudinal systematic observation data to provide a comprehensive description (Johnson, 2001) of a SWPBS system as it was applied in one high school and to increase understanding of universal level implementation of SWPBS in this particular context. Disciplinary incidences as measured by archival office discipline referrals (ODRs) were analyzed and described for each of the three years (one year of baseline data and two years of intervention data) under study. Overall ODR patterns were examined as well as the incidence of disciplinary referrals related to student grade level, gender, and selected disruptive and antisocial discipline categories. The descriptive analysis provided data in both aggregate and disaggregate form to render insights into educational reform, both process and outcome, in one high school. Information on implementation fidelity was provided. The study highlighted areas for improvement within this specific school and indicated that SWPBS may be beneficial at the high school level.
Keywords: discipline; high school; office referrals; positive behavior support; school-wide; school administration; school counseling; secondary education; secondary schools; educational administration